Less is more: New biomimetic approach to control spatial and temporal cell loading for tissue engineering. Issue 11 (28th January 2014) - Deng, Dan; Liu, Wei; Cheema, Umber; Mudera, Vivek; Hadjipanayi, Ektoras; Brown, Robert A.
Abstract It is increasingly recognized that use of stiff biodegradable polymers in connective tissue engineering has an inherent flaw. Although polymer stiffness has early benefit for mechanical strength of implants, such pseudoprosthetic material function inevitably stress shields embedded cells, switching off their synthetic/remodeling functions. This core conundrum represents a tension between early mechanical benefits of polymer stiffness against blocking of cell load‐dependent matrix production. In effect, an ideal system would produce a gradual, transfer of load onto resident cells and their matrix. Toward this target, our "less is more" (LiM) hypothesis proposes that less stress shielding (polymer stiffness) will lead to more cell‐dependent tissue formation. To test this we have designed a hybrid segregation solution in which the cells are segregated into a native (but weak) collagen–gel matrix while the external mechanical loading is taken by temporary, reinforcing polyglycolic acid (PGA) fibers, with gradual, load transfer as the polymer µ‐fibers fracture. Dermal fibroblasts grew predictably in the hybrid construct and the fine, parallel PGA fibers fractured and fragmented due to hydrolysis, giving a fall of construct stiffness to near collagen‐only levels, over 14 days. The same fiber fracture and fall in stiffness occurred over 14 days in constructs implanted in vivo. In this case a cell dependent, net enhancement of connective tissue stiffness could be identified in hybrid constructs, supporting the LiM hypothesis for cytomechanical control of matrix. This is the first demonstration of spatiotemporal load transfer as a customizable tool for improved, biomimetic connective tissue engineering. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 4108–4117, 2014.